Cho \(x,\,\,y\) thỏa mãn \({\log _3}\dfrac{{x + y}}{{{x^2} + {y^2} + xy + 2}} = x\left( {x - 9} \right) + y\left( {y - 9} \right) + xy\). Tìm giá trị lớn nhất của biểu thức \(P = \...

Câu hỏi :

Cho \(x,\,\,y\) thỏa mãn \({\log _3}\dfrac{{x + y}}{{{x^2} + {y^2} + xy + 2}} = x\left( {x - 9} \right) + y\left( {y - 9} \right) + xy\). Tìm giá trị lớn nhất của biểu thức \(P = \dfrac{{3x + 2y - 9}}{{x + y - 10}}\) khi \(x,\,\,y\) thay đổi. 

A. 2

B. 3

C. 1

D. 0

* Đáp án

A

* Hướng dẫn giải

\(\begin{array}{l}{\log _3}\dfrac{{x + y}}{{{x^2} + {y^2} + xy + 2}} = x\left( {x - 9} \right) + y\left( {y - 9} \right) + xy\\ \Leftrightarrow {\log _3}\left( {x + y} \right) - {\log _3}\left( {{x^2} + {y^2} + xy + 2} \right) + 2 = {x^2} + {y^2} + xy + 2 - 9x - 9y\,\,\left( {x + y > 0} \right)\\ \Leftrightarrow {\log _3}\left( {9x + 9y} \right) + \left( {9x + 9y} \right) = {\log _3}\left( {{x^2} + {y^2} + xy + 2} \right) + {x^2} + {y^2} + xy + 2\,\,\left( * \right)\end{array}\)

Xét hàm số \(f\left( t \right) = {\log _3}t + t\,\,\left( {t > 0} \right)\) ta có \(f'\left( t \right) = \dfrac{1}{{t\ln 3}} + 1 > 0\,\,\forall t > 0 \Rightarrow \) Hàm số đồng biến trên \(\left( {0; + \infty } \right)\).

Từ \(\left( * \right) \Rightarrow f\left( {9x + 9y} \right) = f\left( {{x^2} + {y^2} + xy + 2} \right) \Leftrightarrow 9x + 9y = {x^2} + {y^2} + xy + 2\)

\( \Leftrightarrow 9\left( {x + y} \right) = {\left( {x + y} \right)^2} - xy + 2 \Leftrightarrow xy = {\left( {x + y} \right)^2} - 9\left( {x + y} \right) + 2\)

Ta có: \(x = x + xy - xy = x\left( {y + 1} \right) - xy \le {\left( {\dfrac{{x + y + 1}}{2}} \right)^2} - xy\) \( \Rightarrow xy \le {\left( {\dfrac{{x + y + 1}}{2}} \right)^2} - x\)

Từ đó \(xy = {\left( {x + y} \right)^2} - 9\left( {x + y} \right) + 2 \le {\left( {\dfrac{{x + y + 1}}{2}} \right)^2} - x\) \( \Leftrightarrow x \le {\left( {\dfrac{{x + y + 1}}{2}} \right)^2} - {\left( {x + y} \right)^2} + 9\left( {x + y} \right) - 2\)

Đặt \(t = x + y > 0\) thì

\(\begin{array}{l}P = \dfrac{{x + 2\left( {x + y} \right) - 9}}{{x + y + 10}} = \dfrac{{x + 2t - 9}}{{t + 10}} \le \dfrac{{\dfrac{{{{\left( {t + 1} \right)}^2}}}{4} - {t^2} + 9t - 2 + 2t - 9}}{{t + 10}}\\ = \dfrac{{{t^2} + 2t + 1 - 4{t^2} + 44t - 44}}{{4t + 40}} = \dfrac{{ - 3{t^2} + 46t - 43}}{{4t + 40}}\end{array}\)

Xét hàm số \(f\left( t \right) = \dfrac{{ - 3{t^2} + 46t - 43}}{{4t + 40}}\,\,\left( {t \ne 10} \right)\).

Sử dụng MTCT ta tìm được \(\max P = 2\).

Chọn A.

Copyright © 2021 HOCTAP247